Hand Foot Syndrome Induced by Lenvatinib - A Case Report - Rangshahi, Kiran; Nanda, Siddhartha; Gurunthalingam, Meenalotchini Prakash; Katiyara, Vikas; Thangaraju, Pugazhenthan; Gaikwad, Nitin R (Current Drug Safety, 2025)
Introduction Hand–Foot Syndrome (HFS), also known as palmar–plantar erythrodysesthesia, is a common reaction to Tyrosine Kinase Inhibitors (TKIs), which can often lead to discontinuation of the drug. Lenvatinib is a recently approved drug for the treatment of endometrial carcinoma, which has been proven to provide a better overall survival rate and longer duration of progression-free survival among patients with advanced endometrial cancer. Herein, we have reported a case of carcinoma endometrium with metastasis who had to discontinue the use of lenvatinib due to the adverse drug reaction. Case Report A 60-year-old female patient with carcinoma endometrium with metastasis, post radical hysterectomy with bilateral salpingo–oophorectomy with omentectomy, was started on tablet lenvatinib 8 mg once daily orally for 15 days. After 12 days of treatment, the patient noticed painful lesions with reddish-black discoloration over the left forearm and dorsal aspect of the left hand and fingers, and was diagnosed with lenvatinib-induced hand-foot syndrome. Lenvatinib was discontinued and tab. prednisolone 30mg was taken orally. The reaction subsided after five days. Conclusion Hand-foot syndrome is one of the commonest ADRs due to the use of lenvatinib. Lenvatinib is an oral formulation that patients can take at their homes. Hence, educating patients regarding the HFS is important so that they report it to the treating physicians on time. It is also essential to educate patients regarding the precautions to be taken to avoid hand-foot syndrome. This will help the physicians with the early discontinuation and appropriate treatment with corticosteroids, which will help in improving the quality of life of the patients already suffering from cancer.
Keywords: lenvatinib